Development of reflective competence in students in technical universities of Russia - Panova, Ludmila; Plugina, Natalya; Kaminsky, Alexander; Kondrashova, Elena; Guryanova, Inna; Martynova, Natalya (Journal of Applied Engineering Science, 2018)
One of the main problems of the modern higher education system in the Russian Federation (RF) is underrepresentation of knowledge in the educational process as a factor that determines not only the content of thinking but also the personality content. Hence, it updates the issue of providing pedagogical conditions for the development of students’ ability to reflect, which causes quality changes in the self-awareness structure. Through expansion, its cognitive components ensure positive developments in self-formation of future specialists and their self-adjustment. Based on a literary review, the article analyzes and substantiates the reflection concept content. By means of interviewing, the level of the reflective competence in students in the process of solving problems was analyzed through the example of mechanic engineering students of Russian universities. Based on multidimensional factor analysis, structural (constructive and situational-destructive) factors of students’ reflection in the educational process were identified. Student clusters were formed and substantiated by the growth rates of reflective competence factors. The optimal development level of the situational-destructive factor in student reflection in the process of solving problems was determined. Education technologies for developing reflective competence in students were elaborated. Parameters of pedagogical reflection development in the educational process were substantiated. A pedagogical experiment was conducted to assess the effectiveness of the proposed pedagogical conditions for the formation and development of reflective competence in students in the Russian universities under study. The research of the problem of reflection development in students in the higher education system of the Russian Federation makes a certain contribution to pedagogical science and teaching practice and opens up new opportunities for the student educational process.